2016
DOI: 10.1186/s40781-016-0091-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding a by-product feed-based silage on nutrients intake, apparent digestibility, and nitrogen balance in sheep

Abstract: BackgroundLiterature is lacking on the effects of feeding by-product feed (BF)-based silage on rumen fermentation parameters, nutrient digestion and nitrogen (N) retention in sheep. Therefore, this study was conducted to determine the effect of replacing rye straw with BF-based silage as a roughage source on ruminal parameters, total-tract apparent nutrient digestibility, and N balance in sheep.MethodsThe by-product feed silage was composed of spent mushroom substrate (SMS) (45 %), recycled poultry bedding (RP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…An increase of LAB count could be explained by the physiological growth of LAB and the adequate supply of molasses as a substrate. Homofermentative LAB isolated in the tropical area normally could grow well under pH less than 4, and during the first stage of fermentation, while LAB could grow fast with an adequate amount of WSC [8,43]. L. casei TH14 was one of homo-fermentative LAB which may grow well under pH 4 when compared to other epiphytic LAB and produced high lactic acid concentration with lowering the pH value.…”
Section: Microorganism Countmentioning
confidence: 98%
“…An increase of LAB count could be explained by the physiological growth of LAB and the adequate supply of molasses as a substrate. Homofermentative LAB isolated in the tropical area normally could grow well under pH less than 4, and during the first stage of fermentation, while LAB could grow fast with an adequate amount of WSC [8,43]. L. casei TH14 was one of homo-fermentative LAB which may grow well under pH 4 when compared to other epiphytic LAB and produced high lactic acid concentration with lowering the pH value.…”
Section: Microorganism Countmentioning
confidence: 98%
“…In this context, we started a project to use SMS as roughage for cattle. It has been reported that the silage containing SMS can be used as a roughage for ruminants [3]- [5], although some adverse effects, such as reduced rumination and chewing activity, were observed [6], which may be because of the shorter fiber length of SMS used in this study: it is well known that there is a positive relationship between fiber length and ruminating time or total chewing time [7], [8]. If this assumption holds true, the above problem may be solved when materials having longer fiber length are used as base materials.…”
Section: Introductionmentioning
confidence: 99%
“…At present, much research has already been conducted on the processing and usage of SMS [8,9]. SMS is considered to be an animal feed with nutritional value, rich in polysaccharides, vitamins, and trace mineral elements [10], which can be easily digested and absorbed by ruminants such as cattle [11] and sheep [12]. We speculate that the sika deer, which is a ruminant animal, could also digest SMS better.…”
Section: Introductionmentioning
confidence: 95%